The Effect of (Mental - Skill) Exercises According to (Surface - Deep) Cognitive Representation to Learning Some Forms Shooting Skill of Handball for Juniors - Ali Radhi Abdul Hussein; Samer Youssef Mtaab; Mohammad Jasim Mohammad (Indian Journal of Forensic Medicine & Toxicology, 2021)
The importance of the research lies in preparing (mental - skillful) exercises according to the cognitive representation (surface-deep), as the researchers believe that they affect the attentional control and side pass skill of handball for junior.Through the researchers’ interest in the handball game and its field follow-up to many training and educational units and matches, they noticed that a large number of young players face difficulty to learning and mastering the some forms of shooting skill, which is difficult to perform and also to meet the needs and requirements of the game. As for the most important conclusions, they were: The duration of the independent variable, represented by exercises (mental _ skillful) distributed over the number of training units, was appropriate in the development of the two experimental research groups learning some forms of shooting skill for juniors. The most important recommendations included: The researchers recommend the adoption of (mental _ skill) exercises because of their high impact on the development of learning some forms of shooting skill for juniors.